AgNPs Embedded Screen Printed Electrodes Modified with Schiff Base Ionophore for Al(III) Determination - Nain, Arjun (My University, 2018)
Disposable screen printed electrodes modified with silver nanoparticles (AgNPs) and Schiff base (JS-1, JS-2, and JS-3) were developed and their electrochemical properties were studied using voltammetric techniques. The optimization of supporting electrolyte and scan rate were studied for these compounds. This sensor worked in optimized conditions with KCl (0.1 M) as supporting electrolyte. Schiff base JS-1 has been explored as voltammetric sensor for the sensitive and selective determination of Al(III) ions with in-situ applications. This voltammetric sensor has detection limit of 0.82 µM. It shows good selectivity for Al(III) over a wide variety of alkali, alkaline earth and heavy metal ions. The proposed voltammetric sensor was successfully applied for determination of Al(III) ions in real life samples.
Master of Science- Chemistry
Keywords: Screen printing electrode; Voltammetry; Heavy metal detection; Silver nanoparticles; ionophore